Ethnopharmacological approaches to Talinum paniculatum (Jacq.) Gaertn. - Exploring cardiorenal effects from the Brazilian Cerrado. (28th June 2019) - Tolouei, Sara Emilia Lima; Palozi, Rhanany Alan Calloi; Tirloni, Cleide Adriane Signor; Marques, Aline Aparecida Macedo; Schaedler, Maysa Isernhagen; Guarnier, Lucas Pires; Silva, Aniely Oliveira; de Almeida, Valter Paes; Manfron Budel, Jane; Souza, Roosevelt Isaias Carvalho; dos Santos, Ariany Carvalho; Silva, Denise Brentan; et al.
Abstract: Ethnopharmacological relevance: Talinum paniculatum (Jacq.) Gaertn. (Talinaceae), popularly known as "major gomes" and "erva gorda", is a non-conventional food plant extensively distributed throughout the Brazilian territory. In Brazilian folk medicine, this species is used as aphrodisiac, to treat gastrointestinal problems, and as a cardioprotective agent. However, there are no reports in the literature proving its cardiovascular effects. Aim: To perform a whole-ethnopharmacological investigation of the cardiorenal properties of the ethanol soluble fraction from T. paniculatum (ESTP) in Wistar rats. Material and methods: First, plant samples were collected, properly identified and a morpho-anatomical characterization was carried out to provide quality control parameters. Then, ESTP was obtained and its chemical profile was determined by LC-DAD-MS. In addition, an acute toxicity assay was conducted in female Wistar rats in order to observe any toxic effects after one single administration. Finally, the diuretic and hypotensive potential of ESTP (30, 100 and 300 mg/kg) were investigated in male rats followed by the evaluation of its possible effects on peripheral vascular resistance. Results: Chemical compounds identified from ESTP were chlorogenic acids, amino acids, nucleosides, O -glycosylated flavones and organic acids. No signs of toxicity as well as no changes in urine volume or electrolyte elimination were observed after ESTP acute treatment. On the other hand, prolonged treatment with all doses of ESTP significantly increased urine volume and electrolyte excretion (Na +, K + and Cl − ) without affecting blood pressure or heart rate. Apparently, these effects are involved with the activation of the small conductance calcium-activated potassium channels contributing to the increase of renal blood flow and glomerular filtration rate. Conclusion: Data presented show important information about the ethnomedicinal properties of T. paniculatum . In addition, the study presents the ESTP as a possible herbal medicine, especially when a sustained diuretic effect is required. Graphical abstract: Image 1